Implementasi Program Pengembangan Pemasok Pendekatan Benchmarking untuk Peningkatan Kinerja - Ali Romdhon; Miftakul Huda; Siti Aisah Azahra; M. Kiki Rifaldi; Muthia Rinjani (CV. ULIL ALBAB CORP, 2025)
Supplier Development Program (SDP) is a key strategy to enhance supplier operational performance and strengthen buyer-supplier relationships. This study aims to evaluate the effectiveness of SDP implementation across various industrial contexts using a benchmarking approach. The methods applied include Pareto analysis for prioritizing critical factors, graph theory to evaluate the relationships between factors, and fuzzy logic to monitor supplier performance trends over time. The results reveal that bilateral communication and direct involvement contribute over 80% to the success of SDP. Information sharing and performance-based incentives also play a significant role in improving supplier performance. The fuzzy logic approach identified significant improvements in the dimensions of quality and on-time delivery, although product innovation showed slower progress. This study highlights the importance of strategically managing SDP by prioritizing key success factors. The findings provide practical guidance for organizations to optimize SDP using a data-driven approach, which not only improves supplier performance but also strengthens long-term buyer-supplier relationships.